1999
DOI: 10.1002/(sici)1096-8628(19990212)82:4<294::aid-ajmg4>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Paternally derived de novo interstitial duplication of proximal 15q in a patient with developmental delay

Abstract: Interstitial duplications of proximal 15q containing the Prader-Willi syndrome/Angelman syndrome (PWS/AS) region have been found in patients with autism or atypical autism. In these cases with an abnormal phenotype, the duplications were maternally derived. Paternal origin of the duplication has been associated with a normal phenotype. We report on a patient who presented with nonspecific developmental delay and partial agenesis of the rostral corpus callosum. Fluorescence in situ hybridization (FISH) studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(27 citation statements)
references
References 20 publications
0
26
0
1
Order By: Relevance
“…Interestingly, in one proband, the duplication was paternal in origin. Paternal duplications are only rarely associated with an abnormal phenotype (Mao and Jalal 2000;Mohandas et al 1999). However, the identification of an additional case suggests that this association may not be coincidental.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Interestingly, in one proband, the duplication was paternal in origin. Paternal duplications are only rarely associated with an abnormal phenotype (Mao and Jalal 2000;Mohandas et al 1999). However, the identification of an additional case suggests that this association may not be coincidental.…”
Section: Discussionmentioning
confidence: 85%
“…Abnormal phenotypes have previously been reported for two paternal duplications (Mao and Jalal 2000;Mohandas et al 1999) and two paternal triplications (Cassidy et al 1996;Ungaro et al 2001). There is further evidence from our families that additional paternal copies of the PWACR may cause an abnormal phenotype.…”
Section: Formation Of Rearrangementsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been very few reports of 15q11-13 duplications involving the paternally inherited chromosome, and most of these cases have been identified after testing the extended family of cases with maternally inherited duplications (Bolton et al, 2001;Cook et al, 1997;Mohandas et al, 1999;Schroer et al, 1998). Individuals with paternal duplications have usually been reported to be mildly affected or unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…The limited available evidence has also suggested that the phenotypic manifestations of inherited duplications that involve the PWACR may result in developmental delay without ASD (Bolton et al, 2001;Mohandas et al, 1999) and may be dependent on the parental origin of the duplication with more marked impairments when the duplication is maternally derived (Bolton et al, 2001;Browne et al, 1997;Cook et al, 1997).…”
Section: Introductionmentioning
confidence: 99%